Lactic acid bacteria a functional approach - Albuquerque, Marcela Albuquerque Cavalcanti de, 1984-; LeBlanc, Alejandra de Moreno de; LeBlanc, Jean Guy (Jean Guy Joseph); Bedani, Raquel (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Lactic acid bacteria (LAB) are a diverse group of bacteria that comprise low GC content Gram-positive cocci or rods that produces lactic acid as the major end product of the fermentation process. Bifidobacterium genera may also be considered as a part of the LABgroup for possessing some similar phenotypical characteristics despite the higher GC content. Thekey feature of LAB metabolismis efficient carbohydrate fermentation. This contributes to the production of several microbial metabolites that result in the improvement offlavor and texture of fermented foods, in addition to its positive impact on the human health when LAB is administered as a probiotic. The book deals with advances made in the functionalities of LAB, such as their effect on vitamin D receptor expression, impact on neurodegenerative pathologies, production of B-vitamins for food bio-enrichment, production of bacteriocins to improve gut microbiota dysbiosis, production of metabolites from polyphenols and their effects on human health, effect on reducing the immunoreaction of food allergens, as biological system using time-temperature to improve food safety, and the use of probiotics in animal feed. The book also reviews the use of LAB and probiotic technologies to develop new functional foods and functional pharmaceuticals.
OCLC-licensed vendor bibliographic record.
Keywords: Lactic acid bacteria; MEDICAL / Nutrition; SCIENCE / Life Sciences / General; TECHNOLOGY / Food Science